2019
DOI: 10.1029/2018jd030229
|View full text |Cite
|
Sign up to set email alerts
|

Budget Analyses of a Record‐Breaking Rainfall Event in the Coastal Metropolitan City of Guangzhou, China

Abstract: To investigate the mechanisms for the record‐breaking rainfall in the coastal metropolitan city of Guangzhou, China during 6–7 May 2017, budget analyses of advection and source/sink terms of the water vapor, potential temperature, and vertical momentum equations were conducted using the model output of a nested very large eddy simulation with the Weather Research and Forecasting model. Results show that the warm and moist air flows from the south and east onshore in the lower troposphere provided the main mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The moisture flux across the boundary i [where i can be w (west), s (south), e (east), and n (north)] of the target region, , is calculated using the following equation (Zhou and Yu, 2005;Huang et al, 2019;Z19):…”
Section: Qflux Imentioning
confidence: 99%
“…The moisture flux across the boundary i [where i can be w (west), s (south), e (east), and n (north)] of the target region, , is calculated using the following equation (Zhou and Yu, 2005;Huang et al, 2019;Z19):…”
Section: Qflux Imentioning
confidence: 99%
“…An FSS of 0 means that the forecast has no skill, whereas an FSS of 1 means the forecast is perfect. The FSS has been widely used for the evaluation of high-resolution precipitation forecasts (e.g., Mittermaier and Roberts 2010;Johnson and Wang 2016;Coniglio et al 2016;Huang et al 2018). Figure 4 shows the ensemble mean FSS in different experiments for a composite reflectivity threshold of 40 dBZ for a box with a width of 8D (16 km 3 16 km; Coniglio et al 2016).…”
Section: A Forecast Skill Score Of Reflectivity Forecastsmentioning
confidence: 99%
“…Because of their ability to sample convective storms at high spatiotemporal resolution, radar measurements of reflectivity and radial velocity are most commonly assimilated for convective-scale NWP (Sun et al 2014). A wide variety of studies have demonstrated the benefits of assimilating such radar data to convective-scale analysis and prediction (Snyder and Zhang 2003;Tong and Xue 2005;Xiao et al 2005;Hu et al 2006;Jung et al 2008;Lu and Xu 2009;Dowell et al 2011;Gao and Stensrud 2012;Thompson et al 2012;Sun and Wang 2013;Johnson et al 2015;Wang and Wang 2017;Degelia et al 2018;Huang et al 2018). However, most of these previous studies generally assimilated radar reflectivity and/or radial velocity data from precipitating regions to investigate their impacts on forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…According to the rainfall evolution, this event can be roughly divided into three convective episodes (Figure 1), of which the second and third episodes were reinitiated from the gust front of the previous episode. Because of the extreme precipitation and subsequent severe flooding produced by this convective event and its forecasting challenges, its convection formation and evolution mechanism has been investigated in several published studies (Huang et al., 2020; Huang, Liu, Liu, Knievel et al., 2019; Huang, Liu, Liu, Li, et al., 2019; Wu et al., 2020; H. Xiao, et al., 2019; Yin et al., 2020). These studies suggested that four possible factors might have played important roles in the occurrence and maintenance of this heavy rainfall event, that is, the supply of southerly warm and moist airflow, the UHI, the mountain ranges in the north of Guangzhou, and the trumpet‐shaped coastline of the Pearl River Delta (PRD) in the south of Guangdong Province.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggested that four possible factors might have played important roles in the occurrence and maintenance of this heavy rainfall event, that is, the supply of southerly warm and moist airflow, the UHI, the mountain ranges in the north of Guangzhou, and the trumpet‐shaped coastline of the Pearl River Delta (PRD) in the south of Guangdong Province. Huang, Liu, Liu, Knievel et al., 2019, Huang, Liu, Liu, Li, et al., 2019 suggested that the trumpet‐shaped topography of the PRD was favorable for the convergence of warm and moist airflow, which continuously provided fuel for severe rainfall, while the UHI was an important factor in determining the timing and location of convection initiation (CI) and concentrating the maximum rain core. However, Yin et al.…”
Section: Introductionmentioning
confidence: 99%